Predictors of prospective suicide attempts in a group at risk of personality disorder following self-poisoning - Cailhol, Lionel; Marcoux, Mariève; Mathur, Anjali; Yrondi, Antoine; Birmes, Philippe (Frontiers in Psychiatry, 2023)
Background Patients with personality disorder (PD) are at risk for suicidal behavior and are frequently admitted for this reason to emergency departments. In this context, researchers have tried to identify predictors of their suicidal acts, however, the studies have been mostly retrospective, and uncertainty remains. To prospectively explore factors associated with suicide attempts (SA) in individuals screened for PD from the ecological context of emergencies. Methods Patients were recruited from two emergency departments after a self-poisoning episode (n=310). PDQ-4+ (risk of PD), TAS-20 (alexithymia), SIS (suicidal intent), H (hopelessness), BDI-13 (depression), AUDIT (alcohol consumption) and MINI (comorbidity) questionnaires were completed. SA over the subsequent two years were identified by mailed questionnaires and hospitals' active files. Logistic regression analyses were performed. Results Having a previous suicidal attempt was linked to a 2.7 times higher chance of recurrence after 6 months, whereas the TAS-20 showed a 1.1 times higher risk at 18 months (OR=1.1) and the BDI at 24 months (OR=1.2). Each one-unit increment in TAS-20 and BDI-13 scores increased the risk of SA by 9.8% and 20.4% at 18 and 24 months, respectively. Conclusions Some clinical features, such as alcohol dependence, suicide intent, and hopelessness, may not be reliable predictors of SA among PD patients. However, in the short term, previous SA and, in the long term, depression and alexithymia may be the most robust clinical predictors to consider in our sample of patients with self-poisoning SA.